2017
DOI: 10.31351/vol26iss2pp41-55
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Ketoprofen Nanosuspension Using Solvent Evaporation Technique

Abstract:   The effective surface area of drug particle is increased by a reduction in the particle size. Since dissolution takes place at the surface of the solute, the larger the surface area, the further rapid is the rate of drug dissolution. Ketoprofen     is class II type drug according to (Biopharmaceutics Classification System BCS) with low solubility and high permeability. The aim of this investigation was to increase the solubility and hence the dissolution rate by the preparation of ketoprofen    … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Polydispersity index analysis: Polydispersity index values determine particle size uniformity, with the lowest value indicating the best uniformity. Polydispersity index is a parameter used to determine the particle size distribution obtained from the particle size analyzer 17 . The range of PDI values (0 -0.05) indicates a monodisperse system, (0.05 -0.08) indicates a nearly monodisperse system, (0.08 -0.7) indicates a mid-range polydisperse system, and > 0.7 indicates a polydisperse system (very polydisperse) 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polydispersity index analysis: Polydispersity index values determine particle size uniformity, with the lowest value indicating the best uniformity. Polydispersity index is a parameter used to determine the particle size distribution obtained from the particle size analyzer 17 . The range of PDI values (0 -0.05) indicates a monodisperse system, (0.05 -0.08) indicates a nearly monodisperse system, (0.08 -0.7) indicates a mid-range polydisperse system, and > 0.7 indicates a polydisperse system (very polydisperse) 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Polydispersity index is a parameter used to determine the particle size distribution obtained from the particle size analyzer 17 . The range of PDI values (0 -0.05) indicates a monodisperse system, (0.05 -0.08) indicates a nearly monodisperse system, (0.08 -0.7) indicates a mid-range polydisperse system, and > 0.7 indicates a polydisperse system (very polydisperse) 17 . In this research, polydispersity index was found ranging from 0.1226±0.2 for F2 to 0.4487±0.2 for F5, as shown in table (3).…”
Section: Resultsmentioning
confidence: 99%
“…The solutions were filtered through a membrane filter (0.45 µm), and the dissolved ketoprofen in each flask was measured spectrophotometrically at a wavelength of 260 nm. Each sample was analyzed in triplicate (Wais et al 2017).…”
Section: Determination Of Ketoprofen Saturation Solubilitymentioning
confidence: 99%
“…The obtained ketoprofen solution was then dripped through a plastic syringe positioned with a needle directly into the PVP solution and Tween 80 which was later added up with distilled water to obtain a final mixture of 20 ml in each formula as shown in Table 1. Next, the temperature of each mixture was maintained at 40 °C and then stirred at 650 revolutions per minute (rpm) on a magnetic stirrer for about one hour to allow the ethanol to evaporate (Wais et al 2017).…”
Section: Preparation Of Conventional and Nano-size Ketoprofen Suspens...mentioning
confidence: 99%
See 1 more Smart Citation